Effectiveness of Physical Exercise in Managing Components of Metabolic Syndrome in Obese Populations: A Systematic Review - Ni Wayan Astiti Pertiwi; Debie Dahlia; Dikha Ayu Kurnia; Riri Maria (GLOBAL HEALTH SCIENCE GROUP, 2025)
Obesity is one of the main contributing factors to metabolic syndrome, which results in an increased risk of chronic diseases such as diabetes mellitus, cardiovascular disease, and other metabolic dysfunctions. Physical exercise has long been recognized as a potential nonpharmacological strategy in reducing metabolic risk factors, but the effectiveness of various types of exercise in managing metabolic syndrome still needs to be further reviewed. This study aims to evaluate the effectiveness of physical activity in managing components of metabolic syndrome in an obese population. Using the PRISMA method of literature searches through Pubmed, Ebsco, Scopus and Wiley databases by using specific word combinations to obtain suitable articles. Inclusion criteria included English language articles published in the last five years (2019-2024), randomized controlled trial type, and discussing physical exercise interventions in obese populations. Of the 893 articles retrieved, 7 were reviewed. Studies show that physical exercise significantly reduced risk components of metabolic syndrome such as blood sugar, insulin, HOMA-IR, visceral fat and improved VO 2 max and quality of life. However, long term success was strongly influenced by the level of adherence to the exercise program. Physical exercise in an effective and safe intervention in reducing the risk of metabolic syndrome in obese individuals.